Towards a pervasive information system for patient triage and referral in emergency departments. (2017) - Bouain, Abdelhadi; Fazziki, Abdelaziz El; Sadgal, Mohammed; Abourraja, Mohamed Nezar
Every day, many people come to emergency departments; the orientation and placement of these patients in a waiting list according to the seriousness of their health conditions is an important task that requires a lot of skilled human resources and time. In addition, some people abuse the system by seeking care for minor problems, which significantly increases the emergency department overcrowding. To facilitate and accelerate the process of triage and referral in emergency departments, we propose to create a pervasive environment with a set of sensors. The information system (IS) of this space must exactly determine the patient's state of health and whether he or she must be presented urgently to a specialist, or may be queued according to a given order of priorities; in some cases, he or she must be referred to specialised emergency (maternity, psychiatry, cardiology, etc.). In this document, we present the architecture, implementation and simulation of our system for triage and referral in emergency departments.